(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper explains the many uses of ‘kanga’ or ‘leso’ as a medium for passing on messages of various types in the day to day life of a Swahili person. The paper explains the shape of the kanga, the various uses and the different expressions (‘names’) which are either poetic idiomatic expressions or prose type. Most of the expressions touch on the themes of religion, weddings, general words of wisdom, caution and admonition, congratulatory messages, parents and their immeasurable love and care, among others. Makala haya yanaeleza umuhimu wa vazi la kanga au leso kama njia ya kupitisha jumbe za ainaaina katika maisha ya Mswahili.Tumeeleza umbo la kanga, matumizi yake anuwai na maneno (‘majina’) yake tofautitofauti ambayo huwa aidha ya kishairi au kinathari. Maneno na kauli hizo hurejelea jumbe za kidini, harusi, maneno ya kawaida ya hekima, tahadhari na kuonya, kupongeza, wazazi na mapenzi yao yasopimika na moyo wao wa kujali, kati ya maudhui mengine.